Role of servitization in transitioning from scarcity to abundance paradigm - Hora, Manpreet (Frontiers in Research Metrics and Analytics, 2022)
Servitization refers to firms that sell an “outcome-as-a-service”, rather than just a physical product. In this study, we first examine how servitization has enabled companies such as Netflix to disrupt industries and transition from offering finite products to delivering relatively abundant services? Second, as firms embark upon servitization, value propositions become much less related to scarcity. This leads to the second research question: what are the value propositions for consumers when the paradigm shifts from ownership to usership? For both these questions, we highlight examples such as Netflix, Amazon Web Services (AWS), and Philips to emphasize on value propositions for the consumer as enhanced customer experience through customization, convenience, and co-creation. Further, we expand on the considerations warranted that include the role of technology, data, and analytics, distribution models for physical versus digital products, and challenges in creating servitization in business models.